PARENTERAL IRON THERAPY IN MALNOURISHED CHILDREN - Iqbal, Muhammad Mahmood; Malik, Bashir Ahmed (Pakistan Armed Forces Medical Journal, 2006)
Objective: To evaluate the safety and efficacy of intravenous iron sucrose complex in the treatment of iron deficiency anemia in malnourished children who are unable to tolerate oral iron supplementation or are unresponsive to oral supplementation because of gastrointestinal dysfunction or iron malabsorption.Design: Prospective interventional study.Place and Duration of Study: This study was carried out at Department of Paediatrics Combined Military Hospital Quetta over 24 months of period from 1st November 2002 to 31st October 2004.Patients and Methods:  Each selected patient was given total calculated amount of iron sucrose complex. The iron deficit was calculated by using following formula: Total Iron Deficit (mg) = Body wt (Kg) x (target Hb - Actual Hb) x 0.24 + Depot Iron (mg). Target Hb is 13 G/dl and depot iron is 15 mg/Kg. Iron sucrose complex was diluted in 0.9% Normal saline and was given intravenously over 3-4 hours. To assess the efficacy of Iron sucrose complex serial samples were analyzed for Hemoglobin (HB], Hematocrit (Hct), Red Blood cell indices, Reticulocyte count and serum Ferritin. Total iron deficit was administered over 2 to 3 weeks time.Results:  A total of 17 malnourished children with weight for age below -2SD, completed intravenous iron sucrose infusion. Tolerance of intravenous iron sucrose was good except in one, who had transient episode of lethargy. Mean Hemoglobin at presentation was 6.6G/dl (Range: 4.9G/dl-8.4G/dl). Six weeks after giving intravenous iron therapy mean Hemoglobin was 10.5 G/dl, with average increase of 3.9G/dl (range 3.0G/dl-5.3G/dl).Conclusion: Intravenous iron supplementation with Iron sucrose complex is quite safe and efficient way of replenishing iron body stores and significantly increasing the hemoglobin concentration in malnourished iron deficient children.